Invisible- Hafsa AlKhudairi/ (3eNaj eQFj(B- (3MaUg GdNVjQjs (2024)
Curator's story- A stream of consciousness with warts and all. This publication was developed during the Intermix Residency | Art and Fashion Reimagined. Intermix is a program by a Saudi Visual Arts Commission in collaboration with Fashion Comission.
Keywords: N4390-5098 Visual Arts. Exhibitions; Saudi Arabia